Tailoring ultrafast singlet fission by the chemical modification of phenazinothiadiazoles - Alagna, Nicolò; Han, Jie; Wollscheid, Nikolaus; Pérez Lustres, José Luis; Herz, Julia; Hahn, Sebastian; Koser, Silke; Paulus, Fabian; Bunz, Uwe H. F.; Dreuw, Andreas; Buckup, Tiago; Motzkus, Marcus (Journal of the American Chemical Society, 2019)
Quantum chemistry and time-resolved spectroscopy are applied to rationalize how singlet fission (SF) is affected by systematic chemical modifications introduced into phenazinothiadiazoles (PTD). Substitution of the terminal aromatic ring of TIPS-tetracene by a thiadiazole group leads to a considerable change in the relative energies of its S1 and T1 states. Thus, in contrast to TIPS-tetracene, SF becomes exothermic for various PTD derivatives, which show S1-2T1 energy differences as high as 0.15 eV. This enables SF in PTD as corroborated by femtosecond transient absorption spectroscopy and TD-DFT calculations. The latter report T-T spectra consistent with thin film UV-vis femtosecond transient absorption of PTDs at long delays. TD-DFT calculations also show that the S1-T1 energy gap can be rationally tuned by introducing N atoms into the aromatic scaffold and by the halogenation of one side ring of the PTD. In addition, the specific S1-to-1(T1T1) electronic coupling depends on the crystal morphology and the electronic properties simultaneously. Thus, both of them govern the strength and the interplay between direct and superexchange couplings, which in the most favorable cases accelerate SF to rate constants beyond (100 fs)−1. Remarkably, direct coupling was found to contribute considerably to the total effective coupling and even to dominate it for some PTDs investigated here. A quantum yield of 200% is obtained on the early picosecond time scale for all compounds studied here, which is reduced to 100% due to triplet-triplet annihilation after a few nanoseconds.
Gesehen am 17.01.2020